2009
DOI: 10.1530/eje-09-0694
|View full text |Cite
|
Sign up to set email alerts
|

Influence of disease control with pegvisomant on sleep apnoea and tongue volume in patients with active acromegaly

Abstract: Objectives: Sleep apnoea has been consistently reported to occur in acromegaly. In uncontrolled patients, the severity of sleep apnoea influences physical activity in the daytime. We investigated the influence of disease activity on tongue volume and sleep apnoea treated with the GH receptor antagonist pegvisomant in poorly controlled patients with acromegaly under octreotide. Design and methods: A total of 12 patients with active acromegaly (six females; six males; mean age 57G15 years; body mass index 29.4G4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
17

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 43 publications
2
24
0
17
Order By: Relevance
“…Pharmacological treatment of acromegaly improves left ventricular hypertrophy and dysfunction (HQ), hypertension (LQ), and obstructive sleep apnoea (MQ). [40][41][42][43][44] However, pharmacological treatment of acromegaly might not improve arthropathy (LQ), and effects on soft-tissue tumours are unknown. New techniques are needed to measure bone and joint integrity to assess better the effects of acromegaly treatment (MQ).…”
Section: Comorbiditiesmentioning
confidence: 99%
“…Pharmacological treatment of acromegaly improves left ventricular hypertrophy and dysfunction (HQ), hypertension (LQ), and obstructive sleep apnoea (MQ). [40][41][42][43][44] However, pharmacological treatment of acromegaly might not improve arthropathy (LQ), and effects on soft-tissue tumours are unknown. New techniques are needed to measure bone and joint integrity to assess better the effects of acromegaly treatment (MQ).…”
Section: Comorbiditiesmentioning
confidence: 99%
“…It has been shown that treatment with octreotide can reduce sleep apnea indices (respiratory disturbance index (RDI)) and tongue volume [3,16]. The same observations could be documented with pegvisomant [8]. The effect of treatment with SSA, pegvisomant and dopaminergic agonists is the result of IGF-I and/or GH-normalization with the consequence of reduced soft tissue swelling of the uvula and the tongue volume, which has a major impact of OSA [17].…”
Section: Discussionmentioning
confidence: 84%
“…Successful treatments by surgery and with SSA, pegvisomant or in combination improved sleep apneas syndrome [3,8,11,15]. It has been shown that treatment with octreotide can reduce sleep apnea indices (respiratory disturbance index (RDI)) and tongue volume [3,16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Согласно данным различных исследователей при АМ чаще встречается ОАС [19,22,23]. Кроме указаний на более высокую распро-страненность ОАС среди пациентов с АМ, в литературе отсутствуют данные о других особенностях клинического течения ОАС у больных АМ по сравнению с пациентами с ОАС без этого заболевания.…”
Section: терапевтический архив 4 2015unclassified